PENGARUH BUDAYA ORGANISASI SEKOLAH, KOMUNIKASI DAN KOMPETENSI GURU TERHADAP KINERJA GURU DI SMK YP SATRYA BUDI KARANG REJO KABUPATEN SIMALUNGUN - Amini Amini; Salim Aktar; Elvira Handayani (Khazanah Pendidikan, 2021)
This study aims to examine the influence of school organizational culture, communication and teacher competence on teacher performance either partially or simultaneously. The sample in this study were teachers of SMK YP Satrya Budi Karang Rejo, Simalungun Regency, totaling 45 people. Data analysis techniques in this study using quantitative techniques. The data in this study are primary data. Data was collected using a questionnaire. The analytical method used is the Multiple Linear Regression model. To test the hypothesis simultaneously the F test is used and partially the t test is used. The results of the tests carried out with SPSS obtained multiple regression equations: Y = 1.822 + 0.179 X1 + 0.207 X2 + 0.237 X3 which means a constant value of 1.822 which indicates that if the school's organizational culture, communication and teacher competence are assumed to be zero, then the value of performance teacher is 1,822. If the independent variable increases by 1%, the teacher's performance will increase. The results of the t-test hypothesis of the research variable are the Organizational Culture variable obtained tcount 2.143 with a significant probability of 0.038 less than the level of confidence (level of significant) = 0.05, Communication variable obtained tcount 2.071 with significant probability 0.045 less than the level of confidence (level of significant) = 0.05, the variable Teacher Competence obtained tcount 2.207 with a significant probability of 0.033 less than the level of confidence (level of significant) = 0.05. So the decision taken is to reject H0 and accept Ha, meaning that school organizational culture, communication and teacher competence have a positive and significant effect on teacher performance at YP Satrya Budi Karang Rejo Vocational School, Simalungun Regency.